Vpliv epidemije COVID-19 na delo v fiziatrični ambulanti in na področju fizioterapije v Termah Ptuj in Ambulanti Tominc - Rauter Pungartnik, Tanja (Rehabilitacija (Ljubljana), 2021)
The epidemic of the new coronavirus had a significant impact on the organisation of work in the outpatient clinic of physical and rehabilitation medicine and in the field of outpatient physiotherapy. We reviewed the articles and found various guidelines for hospital treatment and rehabilitation. We describe the course of re-establishing health services in our rehabilitation centre after closure of all non-essential activities in March 2020. Due to limited contact with patients, the shift of treatment of patients to virtual health followed first. In the provision of outpatient specialist activities, there has been a shift from direct interactions to providing patient care using communication technologies; in the field of outpatient physiotherapy, the scope of the individual approach has increased. It is primarily necessary to provide a safe environment for the patient and medical staff. We found that physiatrist and physiotherapeutic treatment should also be performed during the epidemics. Lack of access to rehabilitation services can lead to a deterioration in functional status and hence to a more difficult return to work and poorer management of daily activities. The function of the PRM specialist as a coordinator and leader of the team approach is important, which influences a better and optimal treatment of the patient according to professional guidelines. We also describe the advantages and disadvantages of the impact of the epidemic on the treatment of patients in our outpatient clinics.
Keywords: ambulantna fizioterapija; COVID-19; outpatient pysiotherapy; rehabilitacija; Rehabilitation; specialistic physiatric clinic; specialistična fiziatrična ambulanta